The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep36852
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthetic (E)-2-methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) phenol inhibits arthritis by targeting signal transducer and activator of transcription 3

Abstract: Rheumatoid arthritis (RA) is a severely debilitating chronic autoimmune disease that leads to long-term joint damage. Signal transducer and activator of transcription 3 (STAT3)-targeted small molecules have shown promise as therapeutic drugs for treating RA. We previously identified (E)-2,4-bis(p-hydroxyphenyl)-2-butenal (BHPB), a tyrosine-fructose Maillard reaction product, as a small molecule with potent anti-inflammatory and anti-arthritic properties, mediated through the inhibition of STAT3 activation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In our study, MMPP inhibited STAT3 DNA binding and transcriptional activity, suggesting that MMPP can inhibit neuroinflammation through inactivation of astrocytes via blocking STAT3-mediated p38 and JNK MAPK pathways. Previously, we reported that MMPP has anti-inflammatory effects in inflammatory disease models such as AD, rheumatoid arthritis, and cancer [29,49,50]. We did not detect any side effects of MMPP with the effective dose of MMPP (5 mg/kg) during treatment for 30 days [29].…”
Section: Discussionmentioning
confidence: 65%
“…In our study, MMPP inhibited STAT3 DNA binding and transcriptional activity, suggesting that MMPP can inhibit neuroinflammation through inactivation of astrocytes via blocking STAT3-mediated p38 and JNK MAPK pathways. Previously, we reported that MMPP has anti-inflammatory effects in inflammatory disease models such as AD, rheumatoid arthritis, and cancer [29,49,50]. We did not detect any side effects of MMPP with the effective dose of MMPP (5 mg/kg) during treatment for 30 days [29].…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have reported that STAT3 involved in numerous inflammatory diseases including RA. STAT3 could interact with NF-κB, and concomitant activation of the STAT3 and NF-κB pathways could exacerbate the inflammatory responses such as those for TNF-α and IL-6, which recruit immune cells to the inflamed synovium and pannus [ 37 ]. STAT3 also plays a pivotal role in RANKL-induced osteoclast formation, a delicately controlled balance by a bioavailable molecule can attenuate RANKL-induced osteoclastogenesis by blocking both NF-κB and STAT3 activity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the effector level of arthritis, apart from targeting effector molecules, like C5 [ 67 , 153 ] and its break down product C5a [ 65 , 154 , 155 ], receptors (FcRs [ 156 ], TLRs [ 157 ]), transcription factors [ 158 , 159 ]), and cytokines, using different strategies and drugs [ 160 , 161 , 162 ], methods for direct targeting of pathogenic IgG antibodies could be attractive and optimal for therapeutic applications.…”
Section: Targeting Igg To Treat Antibody Dependent Pathologiesmentioning
confidence: 99%